Merumuskan Kerangka Aksioma Etik Islam - Jauhar Faradis (Universitas Alma Ata, 2009)
Islamic ethic is representation of axioms that includes four elements namely, unity, equally, independent and responsibility. Ethics also meets all the principal characteristics of the axiom system: minimal, consistent, and independent. The device of this axiom also reflects the central message of the Islamic social philosophy is refusing of the status quo that is not fair and the demands of social change. Analysis used in this chapter is the use of ethical beliefs in a typical Muslim community as a valid logical basis of economic behavior.Key words: Naqvi, Initiating, Economics, Islam.